2015
DOI: 10.14202/vetworld.2015.541-544
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of classical swine fever in Karnataka, India

Abstract: Aim:The present study was conducted to know the current scenario of classical swine fever (CSF) in Bengaluru Urban, Bengaluru Rural, Chikkaballapur, Madikeri, Mandya, Bagalkot, Gadag, Yadgir, Koppal, and Bidar districts of Karnataka with the using of both antigen and antibody ELISA.Materials and Methods:We collected 218 sera and 121 blood samples from pigs from 10 different districts of Karnataka. Screening of sera for CSF IgG antibody and whole blood for CSF virus antigen were carried out using the CSF virus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Search was made using the term “CSF”, “CSF and India” and CSF seroprevalence or CSF prevalence or CSF virus infection in India’ in the CeRA, Google search, and PubMed for searching the databases. The criteria for prevalence study in India and it’s various states were defined as follows: (i) Screening of sera for CSF IgG antibody and whole blood for CSFV antigen carried out using the CSFV antibody and antigen enzyme-linked immunosorbent assay (ELISA) kits, respectively, and virus-specific reverse transcriptase-polymerase chain reaction (RT-PCR) [ 5 , 11 - 15 ]; (ii) Mean prevalence of CSFV antigen in blood samples recorded in different districts of respective states [ 5 , 16 - 20 ]; and (iii) Annual reports of All India Coordinated Research Project on Animal Disease Monitoring and Surveillance (AICRP on ADMAS) on seroprevalence studies of serum samples collected for detection of CSFV-specific antibody by ELISA kits [ 8 , 21 ]. All reference lists from relevant studies were read to locate additional studies but did not contact any authors of original studies for additional information.…”
Section: Methodsmentioning
confidence: 99%
“…Search was made using the term “CSF”, “CSF and India” and CSF seroprevalence or CSF prevalence or CSF virus infection in India’ in the CeRA, Google search, and PubMed for searching the databases. The criteria for prevalence study in India and it’s various states were defined as follows: (i) Screening of sera for CSF IgG antibody and whole blood for CSFV antigen carried out using the CSFV antibody and antigen enzyme-linked immunosorbent assay (ELISA) kits, respectively, and virus-specific reverse transcriptase-polymerase chain reaction (RT-PCR) [ 5 , 11 - 15 ]; (ii) Mean prevalence of CSFV antigen in blood samples recorded in different districts of respective states [ 5 , 16 - 20 ]; and (iii) Annual reports of All India Coordinated Research Project on Animal Disease Monitoring and Surveillance (AICRP on ADMAS) on seroprevalence studies of serum samples collected for detection of CSFV-specific antibody by ELISA kits [ 8 , 21 ]. All reference lists from relevant studies were read to locate additional studies but did not contact any authors of original studies for additional information.…”
Section: Methodsmentioning
confidence: 99%
“…The region is highly prone to the transboundary transmission of exotic CSFV strains. Recent studies have shown that sub-genogroup 1.1 is prevalent in India [6,22], with few reports of genogroup 2 [5,7].…”
Section: Introductionmentioning
confidence: 99%
“…A review of literature on sero-prevalence of CSF in pigs as reported by various authors (Kumar et al, 2007;Jindal et al, 2008;Barman et al, 2012;Ratnaprabha et al, 2012;Deori et al, 2012;Nandi et al, 2011;Shivaraj et al, 2013 andChoori et al, 2015) was carried out to estimate the pooled number of cases of the disease and the Table 7 presents the results of these sero-prevalence studies. In some papers, the seroprevalence was reported for pigs as such without any reference to the age of the animal.…”
Section: Resultsmentioning
confidence: 99%